Host Directed Therapy Against Infection by Boosting Innate Immunity - Bergman, Peter; Raqib, Rubhana; Rekha, Rokeya Sultana; Agerberth, Birgitta; Gudmundsson, Gudmundur H. (Frontiers in Immunology, 2020)
The innate immune system constitutes the first line of defense against invading pathogens, regulating the normal microbiota and contributes to homeostasis. Today we have obtained detailed knowledge on receptors, signaling pathways and effector molecules of innate immunity. Our research constellation has focused on ways to induce the expression of antimicrobial peptides (AMPs), the production of oxygen species (ROS and NO) and to activate autophagy, during the last two decades. These innate effectors, with different mechanisms of action, constitute a powerful defense armament in phagocytes and in epithelial cells. Innate immunity does not only protect the host from invading pathogens, but also regulates the composition of the microbiota, which is an area of intense research. Notably, some virulent bacteria have the capacity to downregulate innate defenses and can thereby cause invasive disease. Understanding the detailed mechanisms behind pathogen-mediated suppression of innate effectors are currently in progress. This information can be of importance for the development of novel treatments based on counteraction of the downregulation; we have designated this type of treatment as host directed therapy (HDT). The concept to boost innate immunity may be particularly relevant as many pathogens are developing resistance against classical antibiotics. Many pathogens that are resistant to antibiotics are sensitive to the endogenous effectors included in early host defenses, which contain multiple effectors working in cooperation to control infections. Here, we review recent data related to downregulation of AMPs by pathogenic bacteria, induction of innate effector mechanisms, including cytokine-mediated effects, repurposed drugs and the role of antibiotics as direct modulators of host responses. These findings can form a platform for the development of novel treatment strategies against infection and/or inflammation.